Futurystyczna uczta literacka (Władimir Sorokin, „Манарага”) - Zywert, Aleksandra (Studia Rossica Posnaniensia, 2019)
In his latest novel Manaraga (2017) Sorokin comments on one of the most significant problems of modern times – the results of the anticipated death of the printed book as well as the related opposition between the original and the copy. The biggest problem, as the author suggests, is not the form of the already published literary classics but the absence of new classics, which can embrace ideas capable of awaking the humankind from its zest for comfort and motivating people for constructive progress.